Stroma AReactive invasion Front Areas (SARIFA) in early-stage oral tongue squamous cell carcinoma - Almangush, Alhadi; Faisal, Muhammad; Haglund, Caj; Kowalski, Luiz Paulo; Hagström, Jaana; Coletta, Ricardo D.; Mäkitie, Antti A.; Salo, Tuula; Leivo, Ilmo (Elsevier, 2026)
Background
Stroma AReactive Invasion Front Areas (SARIFA) has recently been introduced as a prognostic indicator. The prognostic value of SARIFA has not been studied in early-stage oral tongue squamous cell carcinoma (OTSCC).
Material and methods
A total of 287 cases of early-stage OTSCC were included in this multicenter study. SARIFA was defined as direct contact between tumor cells and the adipose tissue, and was assessed in hematoxylin and eosin (HE)-stained sections.
Results
In early-stage OTSCC, SARIFA-positive tumors were associated with worse disease-specific survival with a hazard ratio (HR) of 1.86 (95% CI 1.06–3.28, P = 0.032), overall survival (HR 1.52, 95% CI 1.06–2.19, P = 0.023) and disease-free survival (HR 1.79, 95% CI 1.09–2.93, P = 0.021).
Conclusions
SARIFA is a histomorphology-based prognosticator, that can identify cases with early-stage OTSCC who might benefit from a multimodality treatment protocol.